UCHL3 promotes hepatocellular carcinoma cell migration by de-ubiquitinating and stabilizing Vimentin - Ma, Qiancheng; Lu, Qiliang; Lei, Xiangxiang; Zhao, Jie; Sun, Wen; Wang, Jun; Zhu, Qing; Huang, Dongsheng (Frontiers in Oncology, 2023)
Hepatocellular carcinoma (HCC) is, in the group of common malignant tumors, that have a poor prognosis. UCHL3 has been accounted to participate in the progression of assorted tumors, apart from the molecular mechanisms and biological functions of UCHL3 in HCC stick around the unknown. We institute, in this study, that the expression of UCHL3 was significantly elevated in HCC, which predicted a poor prognosis. We demonstrated that UCHL3 promotes HCC cell migration and stemness-like properties through Transwell and wound healing assays. Then, Vimentin was identified as a potential substrate of deubiquitinase UCHL3 via co-immunoprecipitation and mass spectrometry. Mechanistically, UCHL3 interacted with Vimentin and promoted the deubiquitination of Vimentin, therefore enhancing its protein stability. Moreover, UCHL3 inhibition induced by siRNAs or its inhibitor (TCID), markedly upregulated the ubiquitinated Vimentin. Functionally, Vimentin attenuated the suppression of cell migration caused by the knockdown of UHCL3. In conclusion, UCHL3 is highly expressed in HCC and exerted as an oncogene. We first discovered that Vimentin was a new substrate of UCHL3, and UCHL3 enhances the migration ability of HCC cells by stabilizing the Vimentin protein by deubiquitination.